Research Progress on Energy-saving and Consumption-Reducing Technologies for Plant Factories - Xiang, Jintao (International Journal of Electric Power and Energy Studies, 2025)
As the global food system is under multiple pressures from climate change, resource scarcity and population growth, countries are seeking new solutions. Plant factories, as an important form of controlled environment agriculture, are seen as a key technology to alleviate food supply problems. This article begins by introducing the basic concept of a plant factory. The content includes the definition, classification and core modules of plant factories, while emphasizing the importance of environmental control. Next, the article analyzes how environmental factors such as temperature, relative humidity, and carbon dioxide concentration affect plant growth. This paper further explores the methods of regulating these factors and systematically reviews the key technologies for energy conservation and consumption reduction in plant factories, covering lighting technology, HVAC systems, photovoltaic technology and intelligent control technology. The study shows that by optimizing the spectrum and light intensity, improving the energy form and envelope of the HVAC system, and integrating photovoltaic technology with intelligent control strategies, the energy consumption of plant factories can be significantly reduced and energy utilization efficiency can be improved. Overall, this paper provides a theoretical basis and technical reference for improving the energy efficiency of plant factories and for future related research.